HISTORIOGRAPHIC NOTES: Testamentos as Historical Sources - Del Mundo, Larah Vinda (Diliman Review, 2020)
This brief study scrutinizes the testamento or last will and testament as a historical source. In able to describe the source, examine how it was used as a legal instrument by testators, and what it revealed about the local moral world of the propertied class, ten testamentos from the tail end of the 19th century were translated and summarized. Potential scholarly uses for testamentos were then identified. Key words: 19th Century Philippines, testamentos, last will and testament, death, intergenerational wealth transfer